Green synthesis of fluorescent carbon dots with antibacterial activity and their application in Atlantic mackerel (Scomber scombrus) storage. Issue 4 (2nd February 2022) - Lin, Rong; Cheng, Shasha; Tan, Mingqian
Abstract : Antimicrobial materials prepared from natural products could provide new ways to preserve seafood and extend the shelf life. Abstract : Antimicrobial materials prepared from natural products could provide new ways to preserve seafood and extend the shelf life. Herein, four kinds of fluorescent carbon dots were prepared using onion, ginger, garlic, and fish through one-step hydrothermal synthesis. The four prepared carbon dots were nearly spherical and nanosized, with amorphous structure, neutral charge and good water dispersibility. The onion and garlic carbon dots contained more sulfur elements than the ginger and fish carbon dots. Interestingly, the onion carbon dots exhibited the best antibacterial activity against Pseudomonas fragi with good stability over a wide pH range. In addition, the onion carbon dots also exhibited antimicrobial activity against representative Gram-negative ( Escherichia coli ) and Gram-positive ( Staphylococcus aureus ) bacteria. The minimum inhibitory concentration (MIC) and the minimal bactericidal concentration (MBC) of onion carbon dots against Pseudomonas fragi were 2 mg mL −1 and 4 mg mL −1, respectively. The integrity of the cell wall and the cell membrane were damaged for Pseudomonas fragi, and the extracellular alkaline phosphatase (AKP) and ATP activity also increased after exposure to the onion carbon dots, thus leading to a decrease in the cell viability and alteration of the cellular morphology for Pseudomonas fragi . Furthermore, the preservation effect of onion carbon dots on Atlantic mackerel evaluated by storage at 4 °C revealed that the onion carbon dots significantly reduced drip loss, total volatile basic nitrogen (TVB-N) value and total viable counts (TVC) value, and extended the shelf life of Atlantic mackerel by 2 days. This finding suggests that onion carbon dots have potential to be applied as a bacteriostatic agent for aquatic products.